Synthesis of 2D Tungsten disulphide WS2 for biosensing: a unique perspective on emerging applications - Chih-Chiang Wang; Arvind Mukundan; Riya Karmakar; Kadu Samarth Jalindra; Hsiang-Chen Wang (Discover Nano)
Abstract Two-dimensional (2D) materials have garnered momentous consideration owing to their inimitable structural and physiochemical properties, enabling diverse technological applications. Tungsten disulfide (WS2), a prominent transition metal dichalcogenide, exhibits exceptional characteristics such as a tunable bandgap, large surface area, and strong biocompatibility, making it highly suitable for biosensing applications. This review explores various WS2 synthesis techniques, including mechanical exfoliation, sonication, and chemical exfoliation, highlighting their impact on nanosheet quality and scalability. Furthermore, it examines WS2’s role in biosensing, particularly in cancer biomarker detection, DNA/RNA sensing, enzyme activity monitoring, and pathogen identification. Despite its promising applications, challenges such as oxidation, long-term stability, and large-scale synthesis persist. Future advancements in hybrid nanostructures, functionalization techniques, and AI-assisted biosensing are expected to enhance WS2’s reliability and expand its practical deployment. By addressing these challenges, WS2-based technologies can drive significant innovations in diagnostics and environmental monitoring.